A new insight into more effective viscosupplementation based on the synergy of hyaluronic acid and phospholipids for cartilage friction reduction. (March 2021) - Hilšer, P.; Suchánková, A.; Mendová, K.; Filipič, K. Eleršič; Daniel, M.; Vrbka, M.
Abstract: Osteoarthritis is a joint disease characterized by progressive damage to the cartilage. For a long time, viscosupplements have been based on hyaluronic acid (HA), which is known to relieve the pain of osteoarthritic patients. Recently, however, it has been hypothesized that phospholipids and HA may be collectively responsible for the extremely low friction observed in joint models (mica tape), suggesting that such a combination might lead to more effective viscosupplements. Using a pin-on-plate tribometer, we have tested this hypothesis by analyzing the coefficient of friction of conventional HA viscosupplements compared to the new viscosupplement formula of phospholipids and HA. Our findings show that phospholipids and HA do indeed lead to the lowest friction in the joints at both cartilage-mica tape and cartilage-glass interfaces (joint models). Furthermore, these results also hold true when both viscosupplements are mixed with synovial fluid simulating the real conditions after viscosupplement injection into joints. Therefore, we have validated the synergic effect of phospholipids and HA on lowering the cartilage friction and we further hypothesized that this effect is due to hydration lubrication. We believe these findings might contribute to development of new viscosupplement which would significantly improve the lives of person suffering from osteoarthrosis. Highlights: Cartilage lubricated by viscosupplement based on hyaluronic acid exhibits a relatively high friction. Cartilage lubricated by phospholipids and hyaluronic acid provides low friction supposedly due to hydration lubrication. Adding hyaluronic acid based viscosupplement into the joint (mixing it with synovial fluid) increases friction in joint. Adding phospholipids and hyaluronic acid to synovial fluid provides low friction suggesting a more effective viscosupplement.